Computer-supported collaborative supply chain modelling and simulation: a knowledge-centric approach. (17th December 2007) - Karacapilidis, Nikos; Adamides, Emmanuel D.
The availability of objective information and the accommodation of the different perspectives of stakeholders are critical issues in the collaborative design and/or improvement of a supply chain. To address these issues, this paper presents a collaborative, simulation modelling based approach that comprises a theoretically-founded method for the distributed and asynchronous collaboration of supply chain stakeholders, and a web-based tool to support it. The proposed approach aims at augmenting shared understanding, transparency of individual decisions and trust building along the supply chain through an improved, in terms of quality and buy-in, modelling process. Its application is demonstrated through a real case.